Catalogue of fungi in China 1. New taxa of plant-inhabiting fungi - Shi-Liang Liu; Peng Zhao; Lei Cai; Shan Shen; Hao-Wen Wei; Qin Na; Menghui Han; Renxiu Wei; Yupeng Ge; Haixia Ma; Samantha Chandranath Karunarathna; Saowaluck Tibprommab; et al. (Mycology)
China has a huge area of diverse landscapes and is believed to conceive incredibly high fungal diversity. To systematically and promptly report Chinese fungal species, we initiate the series of Catalogue of fungi in China here. In the first paper of this series, we focus on plant-inhabiting fungi. A total of 33 new taxa are described all over China. These taxa include two new genera, viz. Cremeoefibula and Nothopucciniastrum, 18 new species, viz. Annulohypoxylon lancangensis, Ascotaiwania coffeae, Clitocella neofallax, Coleopuccinia yunnanensis, Cremeoefibula hengduanensis, Crepidotus furcaticystidiosus, C. tomentellus, Diachea macroverrucosa, Helicogloea hangzhouensis, Hyalopsora caprearum, Nemania polymorpha, Phanerochaetella austrosinensis, Physalacria tianzhongshanensis, Setophaeosphaeria panlongensis, Subulicystidium boreale, Trechispora subaraneosa, Vikalpa dujuanhuensis, and Xylaria pteridicola, and 13 new combinations, viz. Nothopucciniastrum actinidiae, N. boehmeriae, N. coriariae, N. corni, N. coryli, N. fagi, N. kusanoi, N. hikosanense, N. hydrangeae-petiolaris, N. miyabeanum, N. styracinum, N. tiliae, and N. yoshinagae. The morphological characteristics and phylogenetic evidence are used to support the establishment of these new taxa and the accuracy of their taxonomic placements. We hope that the series of Catalogue of fungi in China will contribute to Chinese fungal diversity and promote the significance of recording new fungal taxa from China.